PEMBUATAN SEL SURYA TERSENSITASI ZAT WARNA MENGGUNAKAN EKSTRAK KELOPAK BUNGA ROSELLA (Hibiscus sabdariffa) DAN KULIT MANGGIS (Garcinia manggostana) - Aziz, Hermansyah; Alif, Admin; Chairani, Zulfa (Universitas Andalas, 2011)
Vol 5 No 1ABSTRACT The roselle flower and mangosteen pericarp dyes were applied as dye sensitizer for dye-sensitized solar cell. The solar cell was composed of a thin film TiO2 as working electrode, 2B pencil as controle electrode, and I-/I3- as electrode couple. The influence of dipping time of working electrode in dyes extract on the cell efficiency was investigated. The highest efficiency of roselle and mangosteen dye-sensitized solar cells was obtained at 60-minutes dipping, respectively as 0.017% and 0.032%. Characterization of both dyes extract by UV-Vis Spectrophotometry method showed that dyes adsorb in visible region. Keywords: Solar cell, sensitized, dyes, antosianin, TiO2